2021
DOI: 10.3390/plants10030488
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activities of Sesquiterpene-Rich Essential Oils of Two Medicinal Plants, Lannea egregia and Emilia sonchifolia, from Nigeria

Abstract: Lannea egregia (Anacardiaceae) and Emilia sonchifolia (Asteraceae) are plants used in traditional medicine in southwestern Nigeria. The essential oils from the leaves of L. egregia and E. sonchifolia were obtained by hydrodistillation and analyzed by gas chromatography–mass spectrometry. Both essential oils were dominated by sesquiterpenoids. The major components in L. egregia leaf essential oil were α-panasinsen (34.90%), (E)-caryophyllene (12.25%), α-copaene (11.39%), and selina-4,11-diene (9.29%), while E. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…This discovery aligns with similar findings reported by Costa et al [ 65 ], who observed significant antimicrobial activity, primarily attributed to β -eudesmol (51.60 %), in the EO obtained from Guatteria friesiana (W. A. Rodrigues) Erkens & Maas against 11 different microorganisms. The antimicrobial activity associated with Eucalyptus EOs is generally attributed to their abundant presence of oxygenated monoterpenes and sesquiterpenes [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…This discovery aligns with similar findings reported by Costa et al [ 65 ], who observed significant antimicrobial activity, primarily attributed to β -eudesmol (51.60 %), in the EO obtained from Guatteria friesiana (W. A. Rodrigues) Erkens & Maas against 11 different microorganisms. The antimicrobial activity associated with Eucalyptus EOs is generally attributed to their abundant presence of oxygenated monoterpenes and sesquiterpenes [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…26 Senkirkine and doronine, pyrrolizidine alkaloids are und in the aerial portion, and vitamins like riboflavin and niacin are also present. 32 In humans, phenobarbitone is a wellknown anticonvulsant medication used to treat all types of epilepsy (particularly status epilepsy at 10-20 mg/kg), except absence seizures. 23…”
Section: Universal Names Ofmentioning
confidence: 99%
“…Phytochemicals with adequate antibacterial effectiveness are expected to treat microbial illnesses. 32 Various species in the Asteraceae family have been observed to have a superior inhibitory impact against bacteria and fungi, even at low concentrations. 40 They have been utilized from the beginning of time and are mentioned in Ayurvedic texts such as Vaidya Manorama and Arogya kalpadruma.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…The concentration of EO in the hydrolate was unknown, hence, we performed dilutions of the hydrolate in RPMI or Mueller-Hinton culture medium. It has been demonstrated that EO rich in sesquiterpenes can exhibit moderate to high antifungal activities [33][34][35][36]. The growth of C. albicans and MRSA was not altered in the presence of the hydrolate, regardless of the concentration used.…”
Section: Vocs In S Rubra Fruit: a Perspectivementioning
confidence: 99%